The Assessment of Global Wind Power Generation at Jhimpir Pakistan-A Case Study - Abdul Hameed soomro; Maryam Abbasi; Saira Umer; Eman Shaikh (Sir Syed University Research Journal of Engineering and Technology, 2023)
Energy is the key mover for any country’s development. In today’s era, the demand for energy is rapidly increasing and the cost of power is also increasing due to the lack of fossil fuels (coal, gas, and oil). To overcome the increasing demand and worst crises of non-renewable energy resources, the present solution is to move towards renewable energy. Sindh is a province of Pakistan that has the immense capability and prospect of neat and green energy production. The major locations for renewable energy resources are found in the city of Jhimpir, for wind power, in the district of Thatta, Sindh. Wind power generation is clean, eco-friendly, and easily maintainable. Different power companies are intensively taking part in investments to enhance wind generation and overcome the shortage of power in Pakistan. One of the quick promoting renewable energy is wind energy which is founded on freely available natural resources, in Jhimpir Sindh. This study aims to initiate the wind power analysis, total generating capacity, present scenario, and for wind energy present at different sites in Thatta Jhimpir. The comparison between daily data with six-hour data is carried out through statistical analysis at 10m to calculate the wind speed and direction. The private company has carried out the survey to measure the wind speed and compared data from the analysis, reanalysis,and forecast datasets. The geographical location where the mast was installed is 25.1330 N and 67.9950 E. The mast consists of five anemometers for wind speed measurement such as 85m, 60m, 30m, and 10m, and two wind vanes of 83.5m, and 28.5m for measurement of wind direction. The three years of data were used to evaluate the wind data from the datasets for this study. The researchers evaluated the NCEP-NCAR data in the Gharo region using the WRF simulated model at the height of 10m and 30m. In this study, we have analyzed the five datasets NCEP-NCAR, 20C, CFSR, GFS, and NCEP-FNL to measure the wind data at the height of 10m.